2012
DOI: 10.1039/c2lc20982a
|View full text |Cite
|
Sign up to set email alerts
|

Engineers are from PDMS-land, Biologists are from Polystyrenia

Abstract: As the integration of microfluidics into cell biology research proceeds at an ever-increasing pace, a critical question for those working at the interface of both disciplines is which device material to use for a given application. While PDMS and soft lithography methods offer the engineer rapid prototyping capabilities, PDMS as a material has characteristics that have known adverse effects on cell-based experiments. In contrast, while polystyrene (PS), the most commonly used thermoplastic for laboratory cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
563
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 660 publications
(566 citation statements)
references
References 134 publications
(170 reference statements)
3
563
0
Order By: Relevance
“…Second, PDMS is biocompatible and rather inexpensive. [2][3][4][5] It is common to use PDMS to fabricate channels for the immersion of nanostructure for sensing applications, such as ring resonators and photonic crystals. [6][7][8][9] Unfortunately, PDMS also has some limitations, 10 in particular when considering high-resolution imaging.…”
mentioning
confidence: 99%
“…Second, PDMS is biocompatible and rather inexpensive. [2][3][4][5] It is common to use PDMS to fabricate channels for the immersion of nanostructure for sensing applications, such as ring resonators and photonic crystals. [6][7][8][9] Unfortunately, PDMS also has some limitations, 10 in particular when considering high-resolution imaging.…”
mentioning
confidence: 99%
“…However, the scalability of the PVA mould printing and the scaffold casting process that we have demonstrated in our previous work [25], mean that the method proposed in this paper can generate dual-pore scaffolds with dimension relevant for the size required for creating artificial organs. We used the biocompatible and non-biodegradable elastomeric PDMS, which is widely used in biological and medical applications [28,29], to demonstrate the ease of fabrication to obtain different porous scaffolds for tissue engineering applications. It has already been shown that PDMS scaffolds have the potential to support long-term growth of liver cells [25].…”
Section: Scaffold Fabricationmentioning
confidence: 99%
“…Widely used PDMS materials need to be improved or replaced to achieve higher resistance to chemicals, as well as maintain high compatibility with soft lithography techniques and biological cells. (85) In terms of controllability, the automation of both organ-on-a-chip fabrication and screening need to be standardized and optimized. Bio-computer-aided design and manufacturing (Bio-CAD and Bio-CAM) should be introduced to accelerate the design flow of organ-on-a-chip systems.…”
Section: Challenges and Future Directionmentioning
confidence: 99%